Risk status and traumatic birth perception in pregnancy - BİLGİN, ZÜMRÜT (WILEY, 2021)
Objective In this study, the effect of high-risk pregnancies on pregnant women's perception of anxiety and traumatic birth was examined. Design and Methods Data in a comparative descriptive study involving 156 pregnant women, collected by pregnant information form, State and Trait Anxiety, and Traumatic Birth Perception Scale. Results It was found that 44.9% of the pregnant women in the study were between the ages of 24-29, 79.5% wanted to give birth normally, and 62.8% feared vaginal delivery. There was a low level of positive correlation between traumatic anxiety and perception of traumatic delivery in high-risk pregnant women, and a moderate positive relationship between traumatic anxiety and traumatic delivery perception in low risk pregnant women (p < 0.05). Practice Implications It is recommended to determine the risk factors that will create a perception of traumatic birth in pregnant women and to plan holistic care aimed at preventing traumatic births.
Keywords: anxiety; fear of delivery; risky pregnancy; traumatic birth perception